2024
DOI: 10.1186/s12931-024-02820-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of immune regulators Tollip and surfactant protein A inhibits influenza A virus infection in mice

Niccolette Schaunaman,
Diana Cervantes,
Taylor Nichols
et al.

Abstract: Background Influenza A virus (IAV) infection is a significant risk factor for respiratory diseases, but the host defense mechanisms against IAV remain to be defined. Immune regulators such as surfactant protein A (SP-A) and Toll-interacting protein (Tollip) have been shown to be involved in IAV infection, but whether SP-A and Tollip cooperate in more effective host defense against IAV infection has not been investigated. Methods Wild-type (WT), Tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Single cell sequencing of cells derived from PCLS showed that vaping extract amplified influenza-induced inflammatory responses [ 11 ]. Studies also examined the effects of specific inhibitors of multiple pathways to treat influenza infection and its effects [ 12 15 ], as well as to provide information on fundamental ways in which the lung responds to influenza infection [ 16 20 ]. Exposure to some species-specific viruses, including canine distemper virus [ 21 ] and murine pneumonia virus [ 22 ], have also been examined using PCLS.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell sequencing of cells derived from PCLS showed that vaping extract amplified influenza-induced inflammatory responses [ 11 ]. Studies also examined the effects of specific inhibitors of multiple pathways to treat influenza infection and its effects [ 12 15 ], as well as to provide information on fundamental ways in which the lung responds to influenza infection [ 16 20 ]. Exposure to some species-specific viruses, including canine distemper virus [ 21 ] and murine pneumonia virus [ 22 ], have also been examined using PCLS.…”
Section: Introductionmentioning
confidence: 99%